Finite element analysis of bending and torsional loading of two different endodontic rotary files with different off-center geometric sections - Eskibaglar, Mehmet; Erdem, Serkan; Kaman, Mete Onur; Ocak, Mevlut Sinan (Walter de Gruyter Gmbh, 2023)
The aim of this study was to evaluate the performance of two endodontic rotary files with different off-center geometries in bending and torsional tests using finite element analysis (FEA). Trunatomy Prime (TRN-P) and WaveOne Gold Primary (WOG-P) files were used in the study. Geometric models for finite element analysis were obtained by micro-computed tomography scanning. FEA analyses were performed according to ISO 3630-1 specifications to evaluate the bending and torsional tests of the files. Trunatomy Prime showed higher flexibility than WOG-P when subjected to bending. In terms of torsional strength, WOG-P showed higher torsional strength than TRN-P. The geometry of a rotary instrument file influences the mechanical behavior (bending and torsion) of rotary files. The clinician should be aware of the behavioral differences in rotary files and use the appropriate file according to the clinical situation in addition to the manufacturer's instructions.
Keywords: bending and torsional loading; clinical fatigue; cross section; endodontic devices; finite element analysis